Studies on Homalomeneae (Araceae) of Borneo XXII: a new species of Homalomena [Chamaecladon clade] from Kionsom Waterfall, Sabah, Malaysian Borneo - Kartini Saibeh; Peter C. Boyce; Sin, Yeng Wong (Firenze University Press, 2019)
Homalomena kionsomensis Kartini, P.C. Boyce & S.Y.Wong is described and illustrated as a new species of the Chamaecladon clade, and compared with the one other species of the clade so far described from Sabah. Recognition of H. kionsomensis takes the Homalomena flora of Sabah to seven species, five of them described within the last decade. A key to described species is provided.